2004
DOI: 10.4049/jimmunol.173.5.3482
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Markedly Up-Regulates β-Defensin-2 Expression in Human Airway Epithelium via JAK and NF-κB Signaling Pathways

Abstract: Using microarray gene expression analysis, we first observed a profound elevation of human β-defensin-2 (hBD-2) message in IL-17-treated primary human airway epithelial cells. Further comparison of this stimulation with a panel of cytokines (IL-1α, 1β, 2–13, and 15–18; IFN-γ; GM-CSF; and TNF-α) demonstrated that IL-17 was the most potent cytokine to induce hBD-2 message (>75-fold). IL-17-induced stimulation of hBD-2 was time and dose dependent, and this stimulation also occurred at the protein level. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
315
4
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(337 citation statements)
references
References 60 publications
15
315
4
3
Order By: Relevance
“…Other potential roles of IL-17A in asthmatic airways might include the stimulation of mucus cell differentiation 25,41 and induction of chemokine and nitric oxide release. 22,23,30,42 Our study suggests that coexistence of T H 2 cytokines and IL-17A might have a significant effect on the pathogenesis of asthma by positively modulating the existing T (Fig 6, B and C). However, STAT6 nuclear translocation and IL-19 promoter binding were similar in IL-13-and IL-13/IL-17A-treated cells, despite the fact that IL-17A/IL-13-cotreated cells express much higher IL-19 compared with IL-13 alone.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Other potential roles of IL-17A in asthmatic airways might include the stimulation of mucus cell differentiation 25,41 and induction of chemokine and nitric oxide release. 22,23,30,42 Our study suggests that coexistence of T H 2 cytokines and IL-17A might have a significant effect on the pathogenesis of asthma by positively modulating the existing T (Fig 6, B and C). However, STAT6 nuclear translocation and IL-19 promoter binding were similar in IL-13-and IL-13/IL-17A-treated cells, despite the fact that IL-17A/IL-13-cotreated cells express much higher IL-19 compared with IL-13 alone.…”
Section: Discussionmentioning
confidence: 72%
“…SYBR Greenbased real-time PCR was used to quantify the gene of interest, as described previously. 19,23 Relative expressions of genes of interest were normalized to glyceraldehyde-3-phosphate dehydrogenase or β-actin transcripts.…”
Section: Rna Isolation and Real-time Rt-pcrmentioning
confidence: 99%
“…As intestinal Th17 cells have an important role in antimicrobial immunity, particularly at mucosal sites (88)(89)(90), as well as in sustaining enterocyte homeostasis (89,90), the preferential depletion of Th17 cells in pathogenic HIV/SIV infections may be involved in the damage to the structural and functional integrity of the intestinal barrier and in the loss of control over microbial translocation. Indeed, Favre et al elegantly demonstrated that the early loss of GI Th17 in pathogenic SIV infection is associated with overt signs of disease progression that include enhanced immune activation and T-cell apoptosis, increased levels of circulating alpha interferon (IFN-␣), enhanced transcription of IFN-␣-induced genes, and rapid CD4 ϩ T-lymphocyte depletion (87).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationmentioning
confidence: 99%
“…The other IL-17 family members, IL-17B, IL-17C, IL-17D, and IL-17E, are produced by non-T-cell sources. Because of these properties, the main function of Th17 has thought to be the clearance of extracellular pathogens (10,11).…”
Section: The Discovery Of Th17 Cells In Mice and Humansmentioning
confidence: 99%